God and the new physics - DAvies, Paul (New York Penguin Books, 1983)
The book deals fundamentally with cosmology although throughout the text several sciences are mentioned, such as: physics, mathematics, neurology, and philosophy. It deals with a wide variety of philosophical problems, such as the nature of God, miracles, free will, time, and consciousness. Davies seeks to explain the changing roles of religion and science, and the way in which physics is giving insights into what were once considered solely religious or philosophical questions.
Keywords: Religion and science; Physics religious aspects; Physics